An Analysis of Higher Order Thinking Skills Realization in Reading Comprehension Questions - Aryani, Ervina Juli; Wahyuni, Sri (Language Circle: Journal of Language and Literature, 2020)
The significance of Higher Order Thinking Skills (HOTS) has led many educational stakeholders to include the skill in educational curriculum and more specifically in the subjects that students learn. In the context of learning English, HOTS should be instilled in four language skills, especially reading skill. This skill is vital since students are demanded to be critical of what they read. Therefore, this research aimed at investigating how the reading comprehension questions in English textbooks for three different grades (X, XI, and XII) published by the Ministry of Education and Culture facilitate HOTS. By employing cognitive level of Bloom’s revised taxonomy (2001) and critical thinking task type of Numrich’s sequence (Beaumont, 2010), the questions are analyzed qualitatively. The results reveal that HOTS are realized adequately in the textbook for grade XI. In the textbooks for grade X and XII, HOTS are found in small quantity. Besides, based on Numrich’s sequence, the majority of the questions focus on the text which means that critical thinking-based questions are found in small number. Thus, it is expected that this result assists teachers, textbook writers, and future researchers to engage more on the implementation of HOTS.